1988
DOI: 10.1159/000288065
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Alexithymia and Depressive Symptoms in a Sample of Newly Abstinent Alcoholic Inpatients

Abstract: The purpose of this investigation was to measure alexithymia in 90 newly abstinent alcoholism treatment candidates and to examine the relationship between alexithymia and depressive symptoms. Subjects completed the Schalling-Sifneos Personality Scale (SSPS) and the Beck Depression Inventory (BDI) at the time of application for care. The correlation between subjects’ SSPS scores and their BDI scores was statistically significant (r = ––0.398; p < 0.001). Study participants with high BDI scores tended to be ‘mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 20 publications
7
50
1
2
Order By: Relevance
“…The recent psychometric construct of alexithymia according to the Toronto Alexithymia Scale (TAS) includes the following features: difficul ty in identifying and describing feelings, diffi culty in distinguishing between feelings and the bodily sensations that accompany emo tional arousal, constricted imaginai processes, and a cognitive style characterized by a preoc cupation with the details of external events [2,3], In our previous paper, using the SchallingSifneos Personality Scale for assessing alexi thymia, we found persons with alexithym ie personality traits highly overrepresented among male alcoholic patients [4], Such a find ing was confirmed by two other groups of investigators [5,6], We also suggested that two predisposing factors to alcohol dependence such as family history of alcoholism and alexi thymie personality might determine different clinical features of the disease [7], Commenting on the outcome of alcohol dependence, Goodwin [8] pointed out that there is no compelling evidence that treat ment of this condition is superior to no treat ment, but patient's characteristics rather than treatment seem to be the most important pre dictor of outcome. Other studies have shown that alcoholic patients with severe psychiatric problems did poorly regardless of the type of treatment they received, whereas those with less severe psychiatric problems improved in many types of treatment programs [9,10].…”
Section: Introductionsupporting
confidence: 66%
“…The recent psychometric construct of alexithymia according to the Toronto Alexithymia Scale (TAS) includes the following features: difficul ty in identifying and describing feelings, diffi culty in distinguishing between feelings and the bodily sensations that accompany emo tional arousal, constricted imaginai processes, and a cognitive style characterized by a preoc cupation with the details of external events [2,3], In our previous paper, using the SchallingSifneos Personality Scale for assessing alexi thymia, we found persons with alexithym ie personality traits highly overrepresented among male alcoholic patients [4], Such a find ing was confirmed by two other groups of investigators [5,6], We also suggested that two predisposing factors to alcohol dependence such as family history of alcoholism and alexi thymie personality might determine different clinical features of the disease [7], Commenting on the outcome of alcohol dependence, Goodwin [8] pointed out that there is no compelling evidence that treat ment of this condition is superior to no treat ment, but patient's characteristics rather than treatment seem to be the most important pre dictor of outcome. Other studies have shown that alcoholic patients with severe psychiatric problems did poorly regardless of the type of treatment they received, whereas those with less severe psychiatric problems improved in many types of treatment programs [9,10].…”
Section: Introductionsupporting
confidence: 66%
“…In our regression model, especially women with severe depression were associated with alexithymia. Haviland et al [39]have suggested that alexithymia might provide a significant defence against depression. However, this was not corroborated by the findings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Others view alexithy mia as a defensive measure than can modify emotional pain. Haviland et al [18] found alexithymic responses to vary over time in recovering alcoholics and conceptualized al exithymia as a defense against affective dys phoria. VlcDougall [19] reported alexithy-mia to be a defensive phenomena that devel oped due to early mother-child pathology.…”
Section: Discussionmentioning
confidence: 99%